Objective structured clinical examination in intensive care medicine - Jeyanathan, Jeyasankar; Owens, Daniel (Tfm Publishing, 2016)
This book is not only an essential tool for the rehearsal of OSCEs in preparation for these exams, but also for American and Indian exams, and any other exams within the field of intensive care medicine. The OSCE is a style of examination that requires the candidate to present specific information in a short space of time matched to a prescriptive mark scheme. This book allows candidates preparing for an ICM OSCE to format their knowledge for this type of examination whilst practising and rehearsing against time.